1997
DOI: 10.1136/pgmj.73.861.415
|View full text |Cite
|
Sign up to set email alerts
|

Permanent cardiac pacing in elderly patients with recurrent falls, dizziness and syncope, and a hypersensitive cardioinhibitory reflex

Abstract: SummaryThe study was designed to assess the outcome of treatment with permanent dual-chamber pacing of elderly patients with falls, dizziness and syncope associated with the demonstration of a hypersensitive cardioinhibitory reflex. Questionnaires were sent to patients (and their general practitioners) who had been referred to a regional pacing centre with recurrent falls, dizziness or syncope diagnosed as likely to be secondary to cardioinhibitory carotid sinus syndrome or predominantly cardioinhibitory vasov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…12 Patients with cardiac sarcoidosis and conduction abnormalities have a worse prognosis than that of patients with idiopathic AV block. 286,287 Immunosuppression can result in transient reversal of AV block; however, the reversibility is unpredictable. [287][288][289] As such, it is recommended to proceed with pacing according to the most recent guidelines regardless of AV block reversibility.…”
Section: 286-289mentioning
confidence: 99%
“…12 Patients with cardiac sarcoidosis and conduction abnormalities have a worse prognosis than that of patients with idiopathic AV block. 286,287 Immunosuppression can result in transient reversal of AV block; however, the reversibility is unpredictable. [287][288][289] As such, it is recommended to proceed with pacing according to the most recent guidelines regardless of AV block reversibility.…”
Section: 286-289mentioning
confidence: 99%
“…Cardioinhibitory carotid sinus syndrome (CICSS) is traditionally associated with syncope, but has recently also been implicated in the genesis of falls in older patients (1)(2)(3). Both observational (2,3) and intervention (1) studies have demonstrated this causal role, but the reasons why patients present with falls rather than syncope are unclear.…”
mentioning
confidence: 97%
“…3 Cardioinhibitory and mixed carotid sinus hypersensitivity subtypes are amenable to permanent pacing. The cardioinhibitory subtype is defined by the finding of at least three seconds of asystole during carotid sinus massage; if a fall in systolic blood pressure of more than 50 mm Hg is also present, this defines the mixed subtype 1-4.…”
mentioning
confidence: 99%